Reporting and analysis of Sex and Gender in Transitions of Care for Older Adults: A Methods Study - Park, Hanbyoul; Dewidar, Omar; Tanjong-Ghogomu, Elizabeth; Welch, Vivian (University of Ottawa Journal of Medicine, 2022)
Objectives: Sex and gender based analysis may improve understanding of transitions from long term care to community or health services. Our study aims to assess how sex or gender was reported and analyzed in studies about care transitions for older adults. Methods: We identified longitudinal studies from a 2017 scoping review on factors affecting care transitions of older adults (participants 60 years and older) and assessed transitions from long-term care to community or health services. We used a pretested coding sheet to assess the reporting of sex or gender in 5 sections of the studies: title and abstract, introduction, methods, results, and discussion. Results: We included 20 longitudinal studies conducted in 3 countries (United States, Germany, and Finland ) with the study durations ranging from less than 1 year to 10 years. Almost all of the studies reported sex distribution of the sample (18/20; 90%). Sex or gender was discussed in the background and rationale by three out of 20 studies (15%). Twelve studies (60%; 12/20) planned to control for sex or gender in their statistical analysis. Association of sex with outcomes was reported by 45% (9/20) and 3 studies (15%; 3/20) provided disaggregated data on sex or gender. Conclusion: Almost half of the studies assessing transitions from long-term care to community or health services did not control for sex or gender in their statistical analysis. This may be a missed opportunity for understanding potential sex or gender differences in transitions in care for older adults.